Proceso intercultural en el cuidado del adulto con Hipertensión Arterial. - Palacios Chiriboga, Jessica Estefanía (2022)
According to the World Health Organization (WHO), arterial hypertension (AHT) is a chronic condition that mainly affects the pressure exerted by the blood on the arterial walls. It is currently considered a serious health problem worldwide, as it affects all countries with varying degrees of health problems and its prevalence varies according to age, sex, social group, population, dietary and cultural habits. In response to this problem, global goals have been implemented to reduce the occurrence of chronic non-communicable diseases, in the case of hypertension it is estimated that by 2025 it will be reduced by 25% compared to 2010 baseline data. In the Latin American context, the prevalence of hypertension has increased. The Pan American Health Organization estimates that in Ecuador about 45.2% of hypertensive patients do not know if they suffer from this disease, 12.6% know their status but do not comply with their treatment, 16.2% continue with their therapeutic regimen however, they continued to have high blood pressure and only 26% are under control. In the province of Chimborazo, the prevalence of hypertension between 18 to 59 years is 1.8%. The present work is a documentary study, through a systemic review of documents published in electronic databases, in sites related to health issues, as well as national and international organizations and university repositories, with the aim of determining intercultural processes in arterial hypertension adults care, the time interval includes the months of November 2021 to April 2022. For the application of intercultural processes, the application of ancestral knowledge such as: ancestral medicine, alternative or therapeutic treatments with an intercultural approach.